Cover Feature: Electrochemical Oxidative C(sp2)–H Bond Selenylation of Activated Arenes (Eur. J. Org. Chem. 38/2019). Issue 38 (24th September 2019) - Meirinho, Anne G.; Pereira, Vinícius F.; Martins, Guilherme M.; Saba, Sumbal; Rafique, Jamal; Braga, Antonio L.; Mendes, Samuel R.
Abstract : The Cover Feature shows a city skyline which represents the modernization of the synthetic methods, while the cyclic voltammogram represents the redox activity of the species involved in the reaction. We propose a new electrochemical oxidative assessment for C(sp2)–H selenylation using Pt electrodes, and two mechanistic pathways. Path A: Activated arenes in the presence of KI as electrolyte can provide iodinated aromatic derivatives as intermediaries. Path B: Diselenides in the presence of KI may provide PhSeI as an electrophilic species. Selenylated products were obtained with good to excellent yields. Artwork by Vinicius F. Pereira, coauthor of this paper. More information can be found in the Communication by A. L. Braga, S. R. Mendes et al.